LA LIBERTAD DE ELEGIR: POLÍTICA, GOBERNABILIDAD Y POBREZA EN EL CARIBE COLOMBIANO, 1859-1885 - Alarcón Meneses, Luis (2012)
During the second half of the nineteenth century Colombia was organized through a federal regime (1857-1886), which was composed of nine local authorities called Sovereign States. Three of these entities territorial sovereign status recognized by the Federal Constitution of 1863 and located in the wider Caribbean region, were Bolivar, Magdalena and Panama, this article focuses on historical and political practices partisan confrontations that took place in this territory characterized as a largely mestizo society which had to facehard ship as poverty and violence, which added to other problems of cultural governance would eventually prevent these territories.